2011
DOI: 10.1017/s0317167100011501
|View full text |Cite
|
Sign up to set email alerts
|

Stereopsis in Drug Naïve Parkinson's Disease Patients

Abstract: Background:Motor deficits associated with Parkinson's disease (PD) have been well described, yet little attention has been paid to non-motor symptoms, especially cortical visual dysfunction. We investigated stereopsis, as well as the relationship between stereopsis and other cognitive function, in a sample of PD patients.Methods:We used Titmus stereotest plates for assessing stereopsis. Fifty-nine subjects (29 PD patients and 30 normal controls) were included in this study. The included patients underwent a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Recently, in a small study of PD patients, researchers found stereopsis dysfunction to be related to visual cognitive dysfunction [13]. Interestingly, to date, there has been no simultaneous assessment of the potential influence of peripheral abnormality on stereopsis impairment, which could also be triggered once normal cortex is fed with erroneous information from peripheral pathways such as retinal ganglion cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a small study of PD patients, researchers found stereopsis dysfunction to be related to visual cognitive dysfunction [13]. Interestingly, to date, there has been no simultaneous assessment of the potential influence of peripheral abnormality on stereopsis impairment, which could also be triggered once normal cortex is fed with erroneous information from peripheral pathways such as retinal ganglion cells.…”
Section: Introductionmentioning
confidence: 99%
“…In order to perceive objects accurately, a subject basically needs a normal retina, normal visual acuity and proper alignment of the eyes. Two small studies report a stereopsis prevalence of 42% in PD [55,56].…”
Section: Monocular or Binocular Diplopiamentioning
confidence: 99%
“…Declines with age • Common in the absence of ocular morbidity (Wright and Wormald, 1992) • Decline is marked in those >60 years old (Garnham and Sloper, 2006) Impaired • Common in drug naïve patients (Kim et al, 2011) • Linked to reduction in gray matter volume in the right extra-striate visual cortex (Koh et al, 2013) Some studies limited by not assessing for nor excluding patients with vision affecting eye conditions e.g. Goodale and Haffenden (1998).…”
Section: Depth Perceptionmentioning
confidence: 99%